M6A “Writer” Gene METTL14: A Favorable Prognostic Biomarker and Correlated With Immune Infiltrates in Rectal Cancer - Cai, Changjing; Long, Jie; Huang, Qiaoqiao; Han, Ying; Peng, Yinghui; Guo, Cao; Liu, Shanshan; Chen, Yihong; Shen, Edward; Long, Kexin; Wang, Xinwen; Yu, Jian; et al. (Frontiers in Oncology, 2021)
Rectal cancer (RC) is the leading cause of tumor-related death among both men and women. The efficacy of immunotherapy for rectal cancer is closely related to the immune infiltration level. The N6-methyladenosine (m6A) modification may play a pivotal role in tumor-immune interactions. However, the roles of m6A-related genes in tumor-immune interactions of rectal cancer remain largely unknown. After an evaluation on the expression levels of m6A-related genes and their correlations with the prognosis of rectal cancer patients, we found METTL14 was the only gene to be significantly correlated with prognosis in rectal cancer patients. Therefore, we further observed the impact of METTL14 expression and m6A modification on the immune infiltration in rectal cancer. Our study indicates that low expression of the m6A "writer" gene METTL14 in rectal cancer may lead to the downregulation of m6A RNA modification, thus reducing the level of immune cell infiltration and resulting in poor prognosis. METTL14 expression level is an independent prognostic factor in rectal cancer and is positively correlated with the immune infiltration level. Our study identified METTL14 as a potential target for enhancing immunotherapy efficacy in rectal cancer.